Melatonin in the oral cavity: physiological and pathological implications. (25th March 2014) - Reiter, R. J.; Rosales‐Corral, S. A.; Liu, X. Y.; Acuna‐Castroviejo, D.; Escames, G.; Tan, D.‐X.
<x xml:space="preserve">Abstract</x> Background and Objectives The purpose of this article was to summarize what is known about the function of melatonin in the oral cavity. Material and Methods Databases were searched for the relevant published literature to 30 November, 2013. The following search items were used in various combinations: melatonin, gingiva, periodontium, inflammation, herpes, alveolar bone, periodontal ligament, dental implants, xerostomia, methacrylate, chlorhexidine, cancer. The literature uncovered is summarized herein. Results Salivary melatonin levels exhibit a circadian rhythm with highest values at night. Melatonin has both receptor‐mediated and receptor‐independent actions in cells of the oral cavity. Melatonin is released into the saliva by the acinar cells of the major salivary glands and via the gingival fluid. Functions of melatonin in the oral cavity are likely to relate primarily to its anti‐inflammatory and antioxidant activities. These actions may suppress inflammation of the gingiva and periodontium, reduce alveolar bone loss, abrogate herpes lesions, enhance osteointegration of dental implants, limit oral cancer, and suppress disorders that have a free radical component. Sublingual melatonin tablets or oral melatonin sprays and topical melatonin‐containing gel, if used on a regular basis, may improve overall oral health and reduce mucosal lesions. Conclusion Collectively, the results indicate that endogenously‐produced and exogenously‐applied melatonin are beneficial to the oral cavity.